Probable Deep Erosion by Continental Ice Sheet Melt Water Floods: Chalk Buttes Area of Carter County, Montana, USA - Clausen, Eric (International Journal of Geography and Geology, 2018)
Topographic maps are used to determine erosional landform origins along the Little Missouri River-Powder River drainage divide in the Chalk Buttes areas of Carter County, Montana. Asymmetric drainage divides, drainage divide gaps, and isolated erosional remnants are used to determine a sequence of erosion events beginning with headward erosion of northeast-oriented Little Missouri River tributary valleys and ending with headward erosion of the deeper north-northeast and north-northwest oriented Powder River valley. Gaps notched into present day drainage divides and orientations of valley heads on either side of those gaps suggest many closely spaced southeast-oriented streams flowed across the region immediately prior to being captured by headward erosion of deeper north-oriented valleys. Buttes capped by horizontal Miocene Arikaree sandstones stand 500 feet (152 meters) or more above surrounding Little Missouri River tributary drainage basin elevations while the Powder River valley floor elevation is as much as 800 feet (244 meters) below those surrounding elevations. A water source could not be determined from the map evidence, however the study area is located to the south and west of a known continental ice sheet margin and large southeast-oriented ice-marginal melt water floods should have logically crossed the region.